Turkey - Energy and the Environment : Issues and Options Paper - World Bank (Washington, DC, 2014)
This report represents an initial effort to assist Turkey in developing its energy-environment strategy. It represents the first phase of the Turkey Energy and Environment Review. A previous draft of the paper, translated into Turkish, served as the basic discussion document at an Energy and Environment workshop on the environmental impact of energy development in turkey held in Ankara on November 12, 1999. The five break-out sessions covered improved energy efficiency, inter-fuel substitution, institutional/legal//regulatory measures and market-based instruments, Turkish options to participate in the United Nations Framework Convention on Climate Change (UNFCCC), and improved technologies and practices. This revised version of that paper includes the workshop's main findings and recommendations and discusses the priorities for further work suggested by workshop participants.